Financial Incentives and Nurse Coaching to Enhance Diabetes Outcomes (FINANCE-DM): a trial protocol. Issue 12 (22nd December 2020) - Egede, Leonard E; Walker, Rebekah; Williams, Joni S; Knapp, Rebecca; Dismuke, Clara Elizabeth; Davidson, Tatiana; Campbell, Jennifer A
Abstract : Introduction: Given the burden of diabetes in ethnic minorities and emerging data on the efficacy of financial incentives in type 2 diabetes mellitus (T2DM), it is critical to examine the efficacy of financial incentives across and within racial/ethnic groups. Methods and analysis: This trial is an ongoing 5-year, randomised clinical trial designed to test the efficacy of a F inancial In centives A nd N urse C oaching to E nhance Diabetes Outcomes (FINANCE-DM) intervention composed of (1) nurse education, (2) home telemonitoring and (3) structured financial incentives; compared with an active control group (nurse education and home telemonitoring alone). The study also will evaluate whether intervention effects are sustained 6 months after the financial incentives are withdrawn (ie, 18 months post-randomisation) and whether the intervention is differentially efficacious across racial/ethnic groups. Participants will include 450 adults with a clinical diagnosis of T2DM and HbA1c of 8% or higher who self-identify as White, African American or Hispanic. Participants will be randomised to one of two groups: the FINANCE intervention or Active Control. The location and setting of this study include primary care clinics at the Medical College of Wisconsin (MCW) in Milwaukee, WI and community partner sites affiliated with the Center for Advancing Population Science at MCW. Ethics and dissemination: This trial was approved by IRB at MCW under PRO00033788. Trial registration number: Registration for this trial on the United States National Institute of Health Clinical Trials Registry can be found under ID: NCT04203173 and online (https://clinicaltrials.gov/ct2/show/NCT04203173?id=NCT04203173&draw=2&rank=1 ).